A STUDY TO ASSESS THE EFFECTIVENESS OF PROGRESSIVE MUSCLE RELAXATION ON SLEEP QUALITY AMONG POST MENOPAUSAL WOMEN IN SELECTED COMMUNITY AREA AT SALEM DISTRICT (CAHIERS MAGELLANES-NS, 2024)
Aim: The aim of this study was to assess the effectiveness of progressive muscle relaxation on sleep quality among post menopausal women in selected community area at Salem district.Methods: The quasi-experimental one group pre and post -test control research design was selected for this study. A total of 60 post menopausal women selected by using purposive sampling technique. Individual consent both verbal and written was obtained from post menopausal women. Assessment of the pretest level of sleep quality among post-menopausal women in experimental and control group by using Pittsburgh sleep quality index in both experimental and control group. The interventions are progressive muscle relaxation on experimental group. After the interventions, 21st day, the investigator conducted posttest level of sleep quality among post-menopausal women in experimental and control group by using Pittsburgh sleep quality index in both experimental and control group. Results: The result shows in experimental group, 10(33%) had moderate sleep problem, 13 (43%) had severe sleep problem, 7 (23%) had worse sleep problem, whereas in the control group 10(33%) had moderate sleep problem, 11 (36%) had severe sleep problem, 9 (30%) had worse sleep problem among postmenopausal women and in post test. In experimental group, 25 (83%) had mild sleep problem, 3 (10%) had moderate sleep problem, 2 (7%) had severe sleep problem, whereas in the control group 2 (7%) had mild sleep problem,11 (36%) had moderate sleep problem, 10 (33%) had severe sleep problem, 9 (30%) had worse sleep problem among postmenopausal women.Conclusion: The study concludes that progressive muscle relaxation was more effective on improves sleep quality among post menopausal women.